2018
DOI: 10.1371/journal.pone.0208791
|View full text |Cite
|
Sign up to set email alerts
|

Physiological relevance of epithelial geometry: New insights into the standing gradient model and the role of LI cadherin

Abstract: We introduce a mathematical model of an absorbing leaky epithelium to reconsider the problem formulated by Diamond and Bossert in 1967: whether “… some distinctive physiological properties of epithelia might arise as geometrical consequences of epithelial ultrastructure”. A standing gradient model of the intercellular cleft (IC) is presented that includes tight junctions (TJ) and ion channels uniformly distributed along the whole cleft. This nonlinear system has an intrinsic homogeneous concentration and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It has been his life's work and is (in my view) a triumph of biophysics, theory and experiment. 95,179,180,182,183,[185][186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202] Indeed, Mathias resolved (to my satisfaction) several damaging controversies in epithelial physiology 154,[203][204][205] as he studied water flow in the lens and in a more general context. [206][207][208]…”
Section: The Lens Of the Eyementioning
confidence: 95%
“…It has been his life's work and is (in my view) a triumph of biophysics, theory and experiment. 95,179,180,182,183,[185][186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202] Indeed, Mathias resolved (to my satisfaction) several damaging controversies in epithelial physiology 154,[203][204][205] as he studied water flow in the lens and in a more general context. [206][207][208]…”
Section: The Lens Of the Eyementioning
confidence: 95%
“…It was shown that water transport was impaired under hypertonic conditions when LI-cadherin is reduced [40,41]. Therefore, LI-cadherin might be important for water reabsorption of the gut at intraluminal hypertonic conditions [40,41]. Interestingly, the expression of angulin-2 and -3 did not change after the knockout of angulin-1 as a form of compensation in both cell lines.…”
Section: Angulin-1 Knockout Alters the Expression And Localization Of Other Proteins In Mdck C7 And Ht-29/b6 Cellsmentioning
confidence: 97%
“…Lastly, the expression of LI-cadherin was increased in both KO clones, this could affect the water permeability under our experimental conditions. It was shown that water transport was impaired under hypertonic conditions when LI-cadherin is reduced [40,41]. Therefore, LI-cadherin might be important for water reabsorption of the gut at intraluminal hypertonic conditions [40,41].…”
Section: Angulin-1 Knockout Alters the Expression And Localization Of Other Proteins In Mdck C7 And Ht-29/b6 Cellsmentioning
confidence: 99%
“…(95,179,180,182,183,(185)(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202). Indeed, Mathias resolved (to my satisfaction) several damaging controversies in epithelial physiology (154,(203)(204)(205) as he studied water flow in the lens and in a more general context (206)(207)(208).…”
Section: 1mentioning
confidence: 97%